2016
DOI: 10.1038/npjpcrm.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Managing multimorbidity in primary care in patients with chronic respiratory conditions

Abstract: The term multimorbidity is usually defined as the coexistence of two or more chronic conditions within an individual, whereas the term comorbidity traditionally describes patients with an index condition and one or more additional conditions. Multimorbidity of chronic conditions markedly worsens outcomes in patients, increases treatment burden and increases health service costs. Although patients with chronic respiratory disease often have physical comorbidities, they also commonly experience psychological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Second, we showed that half of the patients belonging to the predominantly metabolic multimorbidity profile used drugs for psychological disorders. This novel finding emphasises that asthma management of these multimorbid patients should consider both physical and mental health dimensions [25]. Third, our results reinforce that the "current one-size-fits-all" therapeutic management in asthma has to be reconsidered towards personalised medicine integrating the multimorbidity dimension [40].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Second, we showed that half of the patients belonging to the predominantly metabolic multimorbidity profile used drugs for psychological disorders. This novel finding emphasises that asthma management of these multimorbid patients should consider both physical and mental health dimensions [25]. Third, our results reinforce that the "current one-size-fits-all" therapeutic management in asthma has to be reconsidered towards personalised medicine integrating the multimorbidity dimension [40].…”
Section: Discussionsupporting
confidence: 74%
“…Our findings have relevant clinical implications. First, among elderly women with asthma, we identified a common subgroup of women with complex multimorbidities (allergic or metabolic), who most likely require a continuity of care by a physician and regular consultations to review their chronic conditions and related medications [25,40]. Second, we showed that half of the patients belonging to the predominantly metabolic multimorbidity profile used drugs for psychological disorders.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Asthma is a world‐wide public health problem associated with a high economic cost and is the second most common chronic illness in primary care with 6.0% of the UK population being actively treated . Comorbidities are important to recognize in people with asthma because they can complicate the clinical care of patients with asthma in a variety of ways . First, comorbidities may present with similar symptoms as those associated with poor asthma control.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Comorbidities are important to recognize in people with asthma because they can complicate the clinical care of patients with asthma in a variety of ways. 3,4 First, comorbidities may present with similar symptoms as those associated with poor asthma control. This could lead to under-or overtreatment of asthma through misdiagnosis, increasing treatment burden and unnecessary cost.…”
Section: Introductionmentioning
confidence: 99%